Ecosystem-based adaptation to climate change: what role for policy-makers, society and scientists? - Vignola, Raffaele; Locatelli, Bruno; Martínez, Celia; Imbach, Pablo A. (2015)
In developing countries where economies and livelihoods depend largely on ecosystem services, policies for adaptation to climate change should take into account the role of these services in increasing the resilience of society. This ecosystem-based approach to adaptation was the focus of an international workshop on "Adaptation to Climate Change: the role of Ecosystem Services" held in November 2008 in Costa Rica. This article presents the key messages from the workshop.